2018
DOI: 10.4491/eer.2018.266
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for cell counting of Microcystis colonies in water resources using a digital imaging flow cytometer and microscope

Abstract: Microcystis sp. is one of the most common harmful cyanobacteria that release toxic substances. Counting algal cells is often used for effective control of harmful algal blooms. However, Microcystis sp. is commonly observed as a colony, so counting individual cells is challenging, as it requires significant time and labor. It is urgent to develop an accurate, simple, and rapid method for counting algal cells for regulatory purposes, estimating the status of blooms, and practicing proper management of water reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
2
12
0
1
Order By: Relevance
“…Physical and chemical stress in WTPs may cause damaged cells and affect taxonomic cell counts [ 7 ], while DNA can be extracted from lysed and dead cells and provide metagenomics shotgun reads [ 49 ]. Despite the advantages of taxonomic cell counts, measurement bias such as misidentification of morphologically similar species, the impact of the conservation agent on biovolume, and the complexity of counting species in aggregates should be considered [ 50 , 51 , 52 ]. In sludge samples, the presence of debris, sediments, and a high number of cells might increase the probability of cross interferences.…”
Section: Resultsmentioning
confidence: 99%
“…Physical and chemical stress in WTPs may cause damaged cells and affect taxonomic cell counts [ 7 ], while DNA can be extracted from lysed and dead cells and provide metagenomics shotgun reads [ 49 ]. Despite the advantages of taxonomic cell counts, measurement bias such as misidentification of morphologically similar species, the impact of the conservation agent on biovolume, and the complexity of counting species in aggregates should be considered [ 50 , 51 , 52 ]. In sludge samples, the presence of debris, sediments, and a high number of cells might increase the probability of cross interferences.…”
Section: Resultsmentioning
confidence: 99%
“…For high throughput sequencing, these limitations include incomplete DNA sequencing libraries or using different libraries to identify genus and species. In the case of microscopic taxonomic cell counts, several sources of uncertainty and error have been identified [ 65 , 66 ]. The morphological similarity among cyanobacteria taxa may lead to overlooking or misidentifying cyanobacteria under the microscope, especially low abundant species [ 5 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study suggested 0.3 mm 3 /L biovolumes as the vigilance level [109]. However, bias related to human error [112], the negative impact of Lugol's iodine on biovolumes [113], cell underestimation/overestimation due to the presence of aggregated cells [114], and the presence of debris and sediments, especially in the sludge samples [56], may affect the results. More importantly, the significant time required for taxonomic cell counts is a major barrier in using them for a real-time/practical approach.…”
Section: Framework Basismentioning
confidence: 99%